Effects of feedstock ratio and organic loading rate on the anaerobic mesophilic co-digestion of rice straw and pig manure. (July 2015) - Li, Dong; Liu, Shengchu; Mi, Li; Li, Zhidong; Yuan, Yuexiang; Yan, Zhiying; Liu, Xiaofeng
Highlights: The optimal feed ratio of rice straw to pig manure was 1:1 based on volatile solids. Stable biogas production was obtained at an organic loading rate of 3–8 kg VS/(m 3 d). Overloaded anaerobic co-digestion was inhibited by volatile fatty acids accumulation. The maximum volumetric biogas production rate was 3.45 m 3 /(m 3 d). Anaerobic digestion foaming was observed at high organic loading rates. Abstract: In order to investigate the effects of feedstock ratio and organic loading rate (OLR) on the anaerobic mesophilic co-digestion of rice straw (RS) and pig manure (PM), batch bottle tests (2.5 L) were carried out at volatile solid (VS) ratios of 0:1, 1:2, 1:1, 2:1, and 1:0 (RS/PM), and continuous bench experiments (40 L) were carried out at OLRs of 3.0, 3.6, 4.2, 4.8, 6.0, 8.0, and 12.0 kg VS/(m 3 d) with optimal VS ratio. The results showed that the optimal ratio was 1:1 in terms of biogas yield. Stable biogas production with an average specific biogas production of 413 L/kg VS was obtained at an OLR of 3–8 kg VS/(m 3 d). Anaerobic co-digestion was severely inhibited by the accumulation of volatile fatty acids when the OLR was 12 kg VS/(m 3 d). Further, light and serious foaming were observed at OLR of 8 and 12 kg VS/(m 3 d), respectively.